Scenario simulation of land exploitation and risk assessment of soil erosion in the low-slope hilly area of the Erhai basin. (October 2017) - Jin, Gui; Deng, Xiangzheng; Yuan, Yongwei; Ma, Sai; Li, Zhaohua; Shi, Saiya
Abstract: Risk assessment of soil erosion is an important prerequisite to develop the low-slope hilly in basin-scale. Using Dynamics of Land System model (DLS), we design the scenario simulation of land exploitation of Dali city which is located in the Erhai basin and typical as low-slope hilly area. Then we bring in Universal Soil Loss Equation (USLE) to assess the risks of soil erosion under different scenarios. In two simulating scenarios, baseline scenario and planning scenario respectively, the spatial distribution pattern of land use of the study area in 2020 shows an overall consistency and a partial difference. The cultivated resources of Dali has been protected since the cultivated land located in dam area has not changed, while construction land has expanded more or less on the basis of existing built-up areas. Specifically, the expansion of construction land in planning scenario is concentrated on Haidong town and Fengyi town where there are rich in low-slope hilly resources. In two scenarios mentioned above, both the value-at-risk of soil erosion and its risk level have no significant rise or drop from 2008 to 2020. As the risk index of soil erosion in baseline scenario is 0.003 taller than in planning scenario, one conclusion can be drawn that the planning scenario will lower the overall risk of soil erosion and should be used to develop gentle hillside area in Erhai basin. The risk evaluation of soil erosion under different scenarios is valuable for land management decisions because the results provide fundamental information for optimal utilization of land use and prevention of ecological risks in the low-slope hilly regions. Highlights: We designed the scenario simulation of land exploitation of Dali City. We used DLS model to analyze LUCC under two different scenarios. We used USLE model to evaluate the risk of soil erosion in low-slope hilly area. Planning scenario will lower the overall risk of soil erosion. The risk evaluation of soil erosion is valuable for land management decisions.